AB0730 Comparison of a single-centre idiopathic inflammatory myopathy cohort from argentina with the euromyositis international registry. (12th June 2018) - Braillard Poccard, A.S.; Gomez, R.; Pino, M.; Garcia Carrasco, M.; Dubinsky, D.
Abstract : Background: The idiopathic inflammatory myopathies (IIM) are rare systemic autoinmune diseases that affect the muscle and other organs. Ttraditionally, IIM encompasses polymyositis (PM) and dermatomyositis (DM), but progressively inclusion body myositis (IBM), Immune-mediated necrotising myopathy (IMNM), the antisynthetase syndrome (ASS) and connective tissue diseases-ovler myositis (CTD-OM) have been recognised within the IIM spectrum Objectives: To compare the clinical characteristics and treatment in a IIM cohort from an Argentinian universitary hospital with the international IIM cohort EUROMYOSITIS Methods: Descriptive, retrospective study. IIM patients defined by expert opinion followed in our centre between October 2007 and October 2017 were included. ASS was defined by the presence of arthritis, raynaud's phenomenon, mechanic hands, elevated CK, muscle weakness, interstitial lung disease and/or presence of antisynthetase antibodies and, as in EUROMYOSITIS, patients with IIM with positive antisynthetase antibodies were reclassified as ASS. CTD-OM was defined as patients with IIM fulfilling classification criteria for other CTD. Demographic data, accumulated clinical features, time interval between disease onset and diagnosis, IIM subtype, treatment and presence of neoplasm were evaluated. Ethnicity was defined using the same classification as in EUROMYOSITIS Results: 58 patients were included: DM 24, PM 4, ASS 10, CTD-OM 20. 89.6% Hispanic, mean age 48.4±15.2 years, median time interval between disease onset and diagnosis 5 months (IQR 2–11 months), been higher in AAS (8.5 months, IQR 1.5–18.2 months). 6, 89% (4/58) patients presented associated neoplasm, 3 with DM and 1 with CTD-OM. Table 1 shows the demographic and clinical features of our IIM cohort and EUROMYOSITIS. Table 2 shows treatments received in our cohort and EUROMYOSITIS. Conclusions: DM was the most frecuent IIM subtype in both cohorts. In our group, CTD-OM was second and ASS was third. Muscle weakness was found less frecuently in our DM and AAS than reported in EUROMYOSITIS. However, calcinosis was more frecuent. This could be explained by our mostly Hispanic population and/or by frecuent Systemic Sclerosis overlap in our patients. It's important to remark that the ethnic variety defined as Hispanic in EUROMYOSITS has a complex composition in Latin America, due to interbreeding. No difference was found in therms of most frecuent treatments between both cohorts. However, use of IVIg was more frecuent in our patients. To our knowledge, this is the first comparative report of an argentinian single-centre IIM cohort and an international multi-centre cohort Disclosure of Interest: None declared